Beverages Sales in Mexico before and after Implementation of a Sugar Sweetened Beverage Tax - Colchero, M. A; Guerrero-López, Carlos Manuel; Molina, Mariana; Rivera, Juan Angel (PLOS ONE, 2016)
Objective To estimate changes in sales of sugar sweetened beverages (SSB) and plain water after a 1 peso per liter excise SSB tax was implemented in Mexico in January 2014. Material and Methods We used sales data from the Monthly Surveys of the Manufacturing Industry from January 2007 to December 2015. We estimated Ordinary Least Squares models to assess changes in per capita sales of SSB and plain water adjusting for seasonality and the global indicator of economic activity. Results We found a decrease of 7.3% in per capita sales of SSB and an increase of 5.2% of per capita sales of plain water in 2014–2015 compared to the pre-tax period (2007–2013). Conclusions Adjusting for variables that change over time and that are associated with the demand for SSB, we found the tax was associated with a reduction in per capita sales of SSB. The effectiveness of the tax should be evaluated in the medium and long term.